PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE NOKIA DENGAN CITRA MEREK SEBAGAI PEMEDIASI - Oktavenia, Kadek Ayuk Riska; Ardani, I Gusti Agung Ketut Sri (E-Jurnal Manajemen; Vol 8 No 3 (2019), 2019)
This study aims to determine the effect of product quality on Nokia mobile phone purchase decision   with brand image as mediator. This   research was conducted in Denpasar   City. The   number of samples taken is 99 samples with  nonprobability sampling method, especially Accidental sampling or convenience sampling. The data were collected through questionnaires with Likert scale 1-5. The analysis technique used is Partial Least Square (PLS) analysis. The results of the study found that product quality has a significant positive effect on purchasing decision, brand   image has a significant positive effect on purchasing   decision, product quality has a significant positive effect on brand image and brand image mediating the effect of product quality on purchasing decision. Companies should conduct market research to make the product or product specifications suitable and suitable to be incorporated in Nokia mobile phone products. In the service, the company must work together with various vendors of Nokia mobile phones both sales and service spare parts, service, and guarantees by multiplying the cooperation with them, with these consumers will easily obtain the services needed.